INSTITUTIONAL STRENGTHENING OF MSMES THROUGH EASY COOPERATIVE PROTECTION - Kusumastuti, Dora (Mimbar Keadilan, 2022)
A Cooperative is a business entity consisting of individuals or legal entities based on their activities based on the cooperative principle as well as a people's economic movement based on the principle of kinship. Raden Aria Wiria Atmadja was recorded in history in 1986 in Purwokerto as a pioneer or at least the inspiration for the establishment of cooperatives in Indonesia, motivated to improve the condition of civil servants, most of whom were in debt from loan sharks. Small, Micro, and Medium Enterprises (MSMEs) as the embodiment of a people's economy are able to contribute to economic growth and absorb labor. The growth of MSMEs with all their problems needs to get support through the establishment of cooperative institutions. This type of normative juridical research with secondary data sources is analyzed using deductive logic. Government Regulation Number 7 of 2021 concerning Ease, Protection, and Empowerment of Cooperatives and MSMEs is a form of support from the government for strengthening MSMEs and cooperatives in Indonesia. Support for MSMEs and cooperatives is provided by the distribution of authority to the central government and local governments in supporting the growth of cooperatives and MSMEs.